2016
DOI: 10.1371/journal.pone.0153324
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of miRNAs and Their Corresponding miRNA Genes in Atlantic Cod (Gadus morhua): Use of Stable miRNAs as Reference Genes Reveals Subgroups of miRNAs That Are Highly Expressed in Particular Organs

Abstract: BackgroundAtlantic cod (Gadus morhua) is among the economically most important species in the northern Atlantic Ocean and a model species for studying development of the immune system in vertebrates. MicroRNAs (miRNAs) are an abundant class of small RNA molecules that regulate fundamental biological processes at the post-transcriptional level. Detailed knowledge about a species miRNA repertoire is necessary to study how the miRNA transcriptome modulate gene expression. We have therefore discovered and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 59 publications
8
44
0
Order By: Relevance
“…18 -24 nt) were mapped to a reference miRNAome (i.e. all of the known mature miRNAs in Atlantic cod) (Andreassen et al, 2016;Bizuayehu et al, 2015), using Novoalign (http://www.novocraft.com), and the mapped sequence reads were counted using a Custom-made script in Python. The reads mapped to the mature reference sequences with edit distance of one or less were considered true mature miRNAs.…”
Section: Deep Sequencing and Analysis Of Deep Sequencing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…18 -24 nt) were mapped to a reference miRNAome (i.e. all of the known mature miRNAs in Atlantic cod) (Andreassen et al, 2016;Bizuayehu et al, 2015), using Novoalign (http://www.novocraft.com), and the mapped sequence reads were counted using a Custom-made script in Python. The reads mapped to the mature reference sequences with edit distance of one or less were considered true mature miRNAs.…”
Section: Deep Sequencing and Analysis Of Deep Sequencing Datamentioning
confidence: 99%
“…While Atlantic cod miRNAs were previously discovered and characterised in early and later life stages (Andreassen et al, 2016;Bizuayehu et al, 2015), there was previously no information on cod miRNAs associated with antiviral immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that miRNA functions are conserved predicts that at least some of the organ-enriched miRNAs in stickleback would also be enriched in the same organ in zebrafish. To test this prediction, we compared the list of organ-enriched miRNAs in stickleback and zebrafish and found that 44 miRNAs were brain-enriched in both species (Figure 3B, D, E), with many of them already known to be brain-associated miRNAs in several fish species 6668 , for example miR9-5p, miR124-3p, and miR138-5p (Figure 4C-E), which are also highly expressed in brain and nervous organs in mammals 45,55,69–73 . These observations suggest a strong evolutionary conservation of function of brain-related, miRNAs among vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…Heart also displayed a significant number of evolutionarily-conserved, organ-enriched miRNAs (12 miRNAs) (Figure 3B, D, E). Heart-enriched miRNAs included mature products of the well-described vertebrate cardiac myomiR genes mir1, mir133 , and mir499 55,67,68,7477 and erythromiRs mir144 and mir451 43 . The former group participate in muscle formation and function, and the latter may reflect the presence of red blood cells in the heart ventricle at the time of RNA extraction.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported 224 miRNAs in Atlantic salmon ( Salmo salar) blood, while the miRbase database lists 371 Atlantic salmon miRNAs, representing at least 11 tissues (Kozomara and Griffiths-Jones, 2014; Kure et al, 2013). More miRNAs have been identified in Atlantic cod ( Gadus morhua ), which has 401 miRNAs from at least nine tissues in miRBase (Andreassen et al, 2016; Kozomara and Griffiths-Jones, 2014). The number of miRNAs identified in these species is influenced by multiple factors, including the diversity of tissues examined, depth of sequencing, and the stringency of criteria used to define bona-fide miR As.…”
Section: Discussionmentioning
confidence: 99%